Anatomy of the endemic palms of the Near and Middle East: archaeobotanical perspectives - Romain Thomas (Revue d'ethnoécologie)
This study presents anatomical descriptors to identify stems and petioles of the Near and Middle East palms genera (Chamaerops, Hyphaene, Medemia, Nannorrhops, Phoenix). Since the Bronze Age, these palms are an essential plant resource for the populations of the hot deserts of these regions. Stems of Phoenix and Hyphaene are used as building materials in architectural work (beams and pillars) and in rare cases as fuel. Woody petioles and midribs of these five genera constitute a common source of fuel, as shown by the many palm fragments found in domestic hearths on archaeological sites. They are also transformed into furniture, small fishing boats or other carpentry works. However, until recently, fragments or remains were identified to the family level – usually interpreted as coming from the date palm – but no attempt had been made to distinguish: (i) the different genera; and (ii) the stem tissue from the woody parts of the leaf (petiole). This work provides positive anatomical descriptors to identify the different structures and the different genera both on carbonized and desiccated material. This study may thereby contribute to the knowledge of human practices of the past.